2015
DOI: 10.3897/compcytogen.v9i1.8804
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of two locariid species (Teleostei, Siluriformes) from Iguatemi River (Parana River drainage) in Brazil

Abstract: Fishes of the Loricariidae family, known as “cascudos”, constitute an endemic group in Neotropical freshwaters. In this study, were cytogenetically examined two species of Loricariidae (Pterygoplichthys anisitsi Eigenmann & Kennedy, 1903 and Farlowella amazonum (Günther, 1864) belonging to Hypostominae and Loricariinae subfamilies respectively) from Iguatemi River. Our study provide the first description regarding C-band and fluorochromic analysis in Farlowella amazonum. In Farlowella amazonum, diploid number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
4
2
0
Order By: Relevance
“…A number of chromosomal rearrangements, such as pericentric inversions and/or deletions are found in the genomes of F. hahni analyzed in this study, given that, although they have the same 2n, the FN value and the karyotypes are different, which the separation geographic and reduced vagility of species, which may lead to the formation of small isolated populations, may have facilitated the establishment of this karyotype variation due to the restriction of gene flow between them. In the Farlowella species analyzed up to now, the nucleolar organizer region (NOR) phenotype is simple, as confirmed by the 18S rDNA probe as shown in Fernandes et al 8,9 and Marajó et al, 10 and the present study. In the karyotype of F. hahni under study, whereas in those of F. schreitmuelleri 10 and F. hahni previous studies, 8,9 the NORs are found on the long arms of the first acrocentric pair, which appears to be a conserved pattern in this genus, except in Farlowella cf.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A number of chromosomal rearrangements, such as pericentric inversions and/or deletions are found in the genomes of F. hahni analyzed in this study, given that, although they have the same 2n, the FN value and the karyotypes are different, which the separation geographic and reduced vagility of species, which may lead to the formation of small isolated populations, may have facilitated the establishment of this karyotype variation due to the restriction of gene flow between them. In the Farlowella species analyzed up to now, the nucleolar organizer region (NOR) phenotype is simple, as confirmed by the 18S rDNA probe as shown in Fernandes et al 8,9 and Marajó et al, 10 and the present study. In the karyotype of F. hahni under study, whereas in those of F. schreitmuelleri 10 and F. hahni previous studies, 8,9 the NORs are found on the long arms of the first acrocentric pair, which appears to be a conserved pattern in this genus, except in Farlowella cf.…”
Section: Discussionsupporting
confidence: 86%
“…In the Farlowella species analyzed up to now, the nucleolar organizer region (NOR) phenotype is simple, as confirmed by the 18S rDNA probe as shown in Fernandes et al 8,9 and Marajó et al, 10 and the present study. In the karyotype of F. hahni under study, whereas in those of F. schreitmuelleri 10 and F. hahni previous studies, 8,9 the NORs are found on the long arms of the first acrocentric pair, which appears to be a conserved pattern in this genus, except in Farlowella cf. amazonum 10 the NOR site is located in the pericentromeric region of the long arms of the first metacentric pair.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…According to Takagui et al (2014) the presence of a few heterochromatic blocks, mainly in the pericentric region, is a remarkable feature of armored catfishes of the subfamily Loricariinae, present in species of the basal genus Harttia (Kavalco et al 2005;Blanco et al 2012) as well as in the derived genus Rineloricaria (Rosa et al 2011;Porto et al 2014b). The exceptions to this pattern are Farlowella amazonum (Fernandes et al 2015) and Loricaria cataprhacta (Porto et al 2014a), which have additional conspicuous terminal heterochromatin blocks in different chromosomes.…”
Section: Discussionmentioning
confidence: 99%